Elevating Shopping Experiences Through Digital Technologies - The Case of Retail Agglomerations - Amela Dizdarevic; Heiner Evanschitzky; Christof Backhaus (Marketing Review St.Gallen, 2018)
Increasingly seizing the opportunities digitalisation offers, physical retail agglomerations such as city centres, shopping centres and High Streets draw on digital applications to elevate customer experiences. From a marketing perspective, the challenge lies in finding and implementing those types of digital applications that consumers find both useful and easy to use. Based on a series of qualitative interviews with shoppers, this article provides a guide to the management of retail agglomerations to successfully digitise their customers' shopping experience.
Keywords: 650